2022
DOI: 10.1111/tpj.15975
|View full text |Cite
|
Sign up to set email alerts
|

TaFDL2‐1A confers drought stress tolerance by promoting ABA biosynthesis, ABA responses, and ROS scavenging in transgenic wheat

Abstract: Plants have developed various protective mechanisms to survive drought stress. Previously, it was shown that a wheat bZIP transcription factor gene TaFD-Like2-1A (TaFDL2-1A) can confer drought tolerance in Arabidopsis. However, the biological functions related to drought stress tolerance of TaFDL2-1A in wheat (Triticum aestivum L.) remain unclear. In the present study, overexpression of TaFDL2-1A in the wheat cultivar Fielder improved drought resistance and conferred abscisic acid (ABA) hypersensitivity. Furth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(17 citation statements)
references
References 73 publications
0
9
0
Order By: Relevance
“…In this study, alkali stress of 30–100 mM resulted in significant increases in the contents of H 2 O 2 , O 2 -, MDA, and EL, which caused serious oxidative damage to N. tangutorum seedlings and significantly reduced the growth indicators, such as plant height, fresh weight(FW), relative water content(RWC), and degree of succulent(DS) ( Figure 1 ). It has been found that multiple environmental stresses stimulate the generation of endogenous ABA and NO in plants, such as drought and alkali stress that induce significant ABA accumulation in wheat and maize, respectively ( Ma et al., 2018 ; Wang et al., 2022 ), which promoted their adaptability to the adverse environment through regulating photosynthesis, antioxidant pathways, ion balance and other pathways. It has been reported that exogenous application of ABA or SNP can effectively promote the production of ABA or NO in plants and reduce the damage caused by stress, such as Brassica pekinensis ( Ren et al., 2020 ), Sorghum bicolor ( Sun et al., 2019 ), and Medicago sativa ( Li, X et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, alkali stress of 30–100 mM resulted in significant increases in the contents of H 2 O 2 , O 2 -, MDA, and EL, which caused serious oxidative damage to N. tangutorum seedlings and significantly reduced the growth indicators, such as plant height, fresh weight(FW), relative water content(RWC), and degree of succulent(DS) ( Figure 1 ). It has been found that multiple environmental stresses stimulate the generation of endogenous ABA and NO in plants, such as drought and alkali stress that induce significant ABA accumulation in wheat and maize, respectively ( Ma et al., 2018 ; Wang et al., 2022 ), which promoted their adaptability to the adverse environment through regulating photosynthesis, antioxidant pathways, ion balance and other pathways. It has been reported that exogenous application of ABA or SNP can effectively promote the production of ABA or NO in plants and reduce the damage caused by stress, such as Brassica pekinensis ( Ren et al., 2020 ), Sorghum bicolor ( Sun et al., 2019 ), and Medicago sativa ( Li, X et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Ten seedlings were analyzed for every treatment, repeated five times. We selected 100 mM alkaline stress as the follow-up experiment ( Wang et al., 2022 ).…”
Section: Methodsmentioning
confidence: 99%
“…The stress-inducible gene BpGRP1 plays a positive role in salt stress tolerance Marked changes in physiology, metabolism and, most notably, gene expression always occur when plants respond to adversity (Gupta et al, 2020;Wang et al, 2022a). Prior research has demonstrated that stress-inducible genes are expressed at higher levels in plants accustomed to coping with salt stress (Li et al, 2022;Xing et al, 2020), and these genes include GRP genes (Tada et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Given that Arabidopsis is an annual herbaceous weed, whilst citrus and kiwifruit are woody perennials from the Rosid and Asterid dicot superclades, respectively, this is indicative of a highly conserved response in eudicots that is likely to be key in overcoming drought stress. Furthermore, experiments with transgenic lines of two monocots, wheat and rice, showed that increased drought tolerance was associated with elevated ABA sensitivity, resulting in greater endogenous ABA accumulation [29,30]. This suggests that the role of ABA in drought tolerance may be conserved across angiosperms as a whole.…”
Section: The Drought Responsementioning
confidence: 99%